Innovations on scientific support of plant breeding for resistance against diseases and pests - Krut, M. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2023)
Goal. Database formation of innovations in the scientific support of plant breeding for resistance against pathogens and pests — grounds for creating sustainable varieties. Methods. Analysis of innovative development of the Institute of Plant Protection of the National Academy of Agrarian Sciences of Ukraine and other institutions of the Scientific and Methodological Center «Protection of Plants» for 2006—2020. Isolation of those relating to the problem of plants’ resistance against pests and pathogens. Results. Methods of plant selection for resistance against the main pathogens and methods of evaluation of resistance of winter wheat, potatoes, clover and alfalfa to pests to create complex resistant varieties have been developed. Donors of potato resistance to canker, alternariosis, phomosis and cyst-forming nematodes were identified. Methods for determining the resistance of cereals to high and low temperatures have been developed. A collection of samples of wild relative of wheat Aegilops biuncilais L. — sources of new genes for plant resistance to diseases and pests. Genes of resistance of soft winter wheat to diseases by DNA markers have been identified. A set of varieties of winter wheat with group and complex resistance against diseases and pests has been formed. Physiological and biochemical mechanisms of resistance of sunflower, soybean, flax oil against pathogens have been established. Collections of sunflower lines based on complex resistance to sunflower broomrape, dry rot, powdery mildew and soybean lines based on complex resistance to white rot and anthracnose have been created. The resistance of forage lupines against the most important pathogens has been studied. Varieties and selection numbers of spring barley, oats, rape, oilseed flax, resistant to major diseases, as well as rice varieties resistant against pathogens and pests were identified. The resistance of modern genotypes of sown hemp, fiber flax and oilseed flax to the main phytophagous insects was evaluated. A method for estimating the selection value of the source material of the main vegetable plants on the basis of disease resistance has been developed. Resistance to viral diseases has been found in cucumber and barley plants. Conclusions. The established innovations can be widely used by breeding centers and other scientific institutions of the agrarian profile when creating sustainable grain, oilseed, vegetable, fodder and leguminous grain crops. In this case, the timing of the selection process can be accelerated by 40—60%.